Correlation of Oxygen Consumption and Patient Day with Invasive Mechanical Ventilation in a Hospital in Sao Paulo during Covid-19 Pandemic - Bin, Kaio Jia; Machado, Luana Alcantara; Junior, Nivaldo Fracacio; Tomazini, Francis Mironescu; de Camargo, Paula Cristina Souto; Hangai, Rosemeire Keiko; Camarotto, Marcelo; Tanaka, Clarice; Pereira, Antonio José Rodrigues (International Journal of Innovative Research in Medical Science, 2021)
Background: The new coronavirus led the world into the pandemic known as COVID-19. Still, without any effective treatment, oxygen therapy is the most used treatment for patients. Without proper management of this medicinal gas, lives can be lost for lack of it. Aim: Find an indicator of a strong correlation with oxygen consumption. Methods: A single-center retrospective study, that evaluated the oxygen consumption billing data and patient-day indicator of Central Institute of HCFMUSP between 2019 and 2020. Results: A total of 380,245 patient days were analyzed. A strong correlation was identified between oxygen consumption and patient day with invasive mechanical ventilation (0.92). An average of 41.6 (± 7.8) cubic meters per patient day with invasive mechanical ventilation was found. Conclusion: There is a strong correlation between oxygen consumption in cubic meters and patient days with invasive mechanical ventilation at the Central Institute of HCFMUSP. The average values of consumption per patient day can help in planning oxygen management in other hospitals.